Meningococcal Sepsis in Patient with Paroxysmal Nocturnal Hemoglobinuria during Pegcetacoplan Therapy - Leo Starck; Vuokko Nummi; Eira Poikonen; Anna-Elina Lehtinen; Pia Kivelä; Nathalie Friberg; Jukka Torvikoski; Maija Toropainen; Seppo Meri (Emerging Infectious Diseases)
Complement C5 inhibitors bring an increased risk for Neisseria infections. A novel complement C3 inhibitor, pegcetacoplan, was recently approved to treat paroxysmal nocturnal hemoglobinuria, a condition commonly treated with complement C5 inhibitors. We present a case of meningococcal sepsis in a pegcetacoplan-treated patient with aplastic anemia and paroxysmal nocturnal hemoglobinuria.